Double-shelled carbon nanocages grafted with carbon nanotubes embedding Co nanoparticles for enhanced hydrogen evolution electrocatalysis. Issue 24 (24th February 2021) - Song, Xue-Zhi; Wang, He; Li, Zhuoxi; Meng, Yu-Lan; Tan, Zhenquan; Zhu, Min
Abstract : Co@CNTs@DSCNCs with a double-shelled hollow structure exhibit an enhanced HER activity compared to a series of Co@CNTs@PC catalysts. Abstract : Herein, small Co nanoparticles (NPs) encapsulated in N-doped double-shelled carbon nanocages grafted with thin carbon nanotubes (Co@CNTs@DSCNCs) were synthesized from yolk–shell bimetallic zeolitic imidazolate framework (BMZIF). For HER electrocatalysis, they exhibit higher activity ( η 10 = 214 mV) and more favorable kinetics than Co@CNTs@PC (PC = porous carbon) with thick CNTs and large Co NPs derived from solid BMZIF cubes.